2001
DOI: 10.1097/00007632-200101150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of OP-1 as a Graft Substitute for Intertransverse Process Lumbar Fusion

Abstract: OP-1 was found to reliably induce solid intertransverse process fusion in a rabbit model at 5 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0
1

Year Published

2004
2004
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 162 publications
(75 citation statements)
references
References 17 publications
5
69
0
1
Order By: Relevance
“…Many studies have examined the effect of exogenous application of a single osteoinductive protein or growth factor to enhance bone repair and regeneration [6,7,14,23]. A potential alternative to the exogenous application of a single factor is a system designed to deliver the cells that have the factors themselves to the desired site.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have examined the effect of exogenous application of a single osteoinductive protein or growth factor to enhance bone repair and regeneration [6,7,14,23]. A potential alternative to the exogenous application of a single factor is a system designed to deliver the cells that have the factors themselves to the desired site.…”
Section: Introductionmentioning
confidence: 99%
“…Because fusion rates of 100% have been seen consistently with OP-1 in this model [8], powered fusion analysis was not a primary objective. Rather, the three animals analyzed were included to confirm that radioactive labeling of OP-1 would not interfere with its osteoinductive properties.…”
Section: Methodsmentioning
confidence: 99%
“…All histologic sections therefore were viewed by one individual (LC) blinded to the results of manual palpation. We selected the 35-day study period because prior investigations have shown fusions to be distinguishable from nonunions by this time [2,8].…”
Section: Methodsmentioning
confidence: 99%
“…They have demonstrated the efficacy of rhBMP-2 and OP-1 as bone substitutes for autografts, resulting in more rapid and reliable healing than that observed in control groups using various carrier matrices in both anterior and posterolateral spinal fusion in nonhuman primate, sheep, and rabbit models [9,11,12,15,38,46,75].…”
Section: Osteoinductive Growth Factorsmentioning
confidence: 99%
“…In an animal study, another major rhBMP, OP-1, was tested in noninstrumented posterolateral fusions and demonstrated high fusion rates [15,38,46,75]. Johnsson et al performed a randomized clinical trial for ensuring OP-1 efficacy in noninstrumented posterolateral fusion as evaluated by radiostereometric analysis.…”
Section: Grade Of Recommendationmentioning
confidence: 99%